Applications of Two-Dimensional Bar Codes and Face Recognition Technologies in the Management of College Student Archives - Lu, Ling Ling; Yang, Yong Wei; Wang, Yong Zhao (International Journal For Research In Educational Studies, 2018)
The two-dimensional bar code technology is widely used in college student archive management systems and has achieved very good results. However, we found that the student identification module in the college student archive management system based on two-dimensional bar code technology requires students to register online to provide too much identity information, and can not check whether the registrants who obtain the student status information are students themselves. In view of the above problems, this paper first analyzes the problems existing in the management of the traditional student archives, and the application value and demand of the two-dimensional bar code technology in the student archives. Combining with the characteristics of the management of college student archives, it is pointed out that the current two-dimensional bar code and face recognition technologies are more suitable for the management of college student archives. The architecture of student status file information management system based on two-dimensional code and face recognition technologies is studied, and the functions of each subsystem are designed.